2019
DOI: 10.1016/j.margeo.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between tidal mudflats and salt marshes affects marsh morphology

Abstract: It is generally assumed that coastal salt marshes are capable of adapting to moderately fast rising sea levels although local sediment availability crucially affects this capability. Whilst there is an increasing awareness that the local sediment availability is inherently related to sediment dynamics on the adjacent tidal mudflat, our current understanding of the interactions between salt marshes and tidal flats is very limited. To address this knowledge gap, we measured suspended sediment concentrations alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 74 publications
0
24
0
Order By: Relevance
“…In this case, a spatial model is deemed necessary. Another problem is to account for temporal variability, e.g., high suspended sediment concentrations during energetic events (Schuerch et al, 2019), which leads to episodic vertical accretion (Goodwin & Mudd, 2019; Reed, 1989). Models for marsh evolution can simulate temporal variability, even though they often face the problem of satisfying mass conservation.…”
Section: Salt Marshes and Sea Level Risementioning
confidence: 99%
“…In this case, a spatial model is deemed necessary. Another problem is to account for temporal variability, e.g., high suspended sediment concentrations during energetic events (Schuerch et al, 2019), which leads to episodic vertical accretion (Goodwin & Mudd, 2019; Reed, 1989). Models for marsh evolution can simulate temporal variability, even though they often face the problem of satisfying mass conservation.…”
Section: Salt Marshes and Sea Level Risementioning
confidence: 99%
“…The influence of waves and storms on deposition near marsh edges has been studied previously based on long-term accretion measurements (Bartholdy et al, 2004;Temmerman et al, 2003;Schuerch et al, 2012) and short-term sediment accumulation (Reed, 1989;Ma et al, 2018). More recently, Ma et al (2018) and Schuerch et al (2019) showed that SSC in the shallows and deposition on the marsh are directly related to wave energy. Duvall et al (2019) found that SSC in bay shallows increases with wave energy but that the effect on sediment supply can be limited if large waves occur at times when the marsh is not inundated.…”
Section: Introductionmentioning
confidence: 99%
“…Without accounting for the sediment import from the ocean, we cannot close the sediment budget for the entire system (Hopkinson et al, 2018). In many systems (e.g., Virginia, USA, and island of Sylt, Germany), it was found that intense storms can resuspend sediments along the shelf and transport them to shallow bays and salt marshes (Castagno et al, 2018;Lacy et al, 2020;Schuerch et al, 2012). The Labrador Current, Warm Core Rings, and the Gulf Stream can also affect the along shelf transport and therefore the marine fluxes of sediment in Plum Island Sound (Townsend et al, 2015;Zhang et al, 2016).…”
Section: 1029/2020gl087862mentioning
confidence: 99%
“…Determining whether costal bays are stable and in equilibrium under SLR requires the quantification of sediment fluxes, and in particular the exchange of material between different geomorphic units like tidal flats and salt marshes (Duvall et al, 2019; French, 2006; Lacy et al, 2020). Sediment inputs are required to accrete tidal flats and salt marshes in addition to organic matter contribution and maintain constant water depths in a period of accelerated SLR (Horton et al, 2018; Schuerch et al, 2019).…”
Section: Introductionmentioning
confidence: 99%